Gold-catalyzed stereoselective domino cyclization/alkynylation of N-propargylcarboxamides with benziodoxole reagents for the synthesis of alkynyloxazolines - Zhao, Ximei; Tian, Bing; Yang, Yangyang; Si, Xiaojia; Mulks, Florian; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2019)
A concise and highly stereoselective synthesis of alkynyloxazolines via a gold-catalyzed domino cyclization-alkynylation cascade of N-propargylcarboxamides with benziodoxole reagents is reported. This new protocol, which represents an attractive alternative to two step sequences based on Sonagashira couplings, offers a broad substrate scope, excellent functional group tolerance, and perfect stereoselectivity. A comparison of the computed energies of the isomers of the product suggests kinetic control as the cause of the observed selectivity.